2021
DOI: 10.3389/fpsyt.2020.568929
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Physical and Mental Health in Lower and Upper Middle-Income Asian Countries: A Comparison Between the Philippines and China

Abstract: Objective: The differences between the physical and mental health of people living in a lower-middle-income country (LMIC) and upper-middle-income country (UMIC) during the COVID-19 pandemic was unknown. This study aimed to compare the levels of psychological impact and mental health between people from the Philippines (LMIC) and China (UMIC) and correlate mental health parameters with variables relating to physical symptoms and knowledge about COVID-19.Methods: The survey collected information on demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 42 publications
(28 reference statements)
0
35
0
Order By: Relevance
“…According to Tee, Salido, et al (2020a), Filipinos reported moderate-to-severe feelings of anxiety, stress, and depression during the early phase of the pandemic. Another study supported this result, which concluded that Filipinos experience increased stress, anxiety, and depression than Chinese people (Tee et al, 2021). Various factors such as gender, age, marital status, occupation, experiencing physical symptoms (such as headache, coughs, and chills), quarantine, staying at home, negative cognitions about personal health and COVID-19, concern for relatives, and feeling discrimination from other countries influence stress and anxiety (Tee, Salido, et al, 2020a).…”
mentioning
confidence: 76%
“…According to Tee, Salido, et al (2020a), Filipinos reported moderate-to-severe feelings of anxiety, stress, and depression during the early phase of the pandemic. Another study supported this result, which concluded that Filipinos experience increased stress, anxiety, and depression than Chinese people (Tee et al, 2021). Various factors such as gender, age, marital status, occupation, experiencing physical symptoms (such as headache, coughs, and chills), quarantine, staying at home, negative cognitions about personal health and COVID-19, concern for relatives, and feeling discrimination from other countries influence stress and anxiety (Tee, Salido, et al, 2020a).…”
mentioning
confidence: 76%
“…Tee et al 31 have compared seven different middle-income countries in Asia and they have found similar risk factors for adverse mental health status. The protecting factors they have established also seemed to be similar within the seven countries.…”
Section: Discussionmentioning
confidence: 99%
“…In order to understand the psychological impact caused by the COVID-19 outbreak, the PHQ-9, and GAD-7 scales were used to measure the symptom severity of depression, and anxiety, respectively. In addition, we used IES-R (a 22-item selfreported scale describing avoidance, intrusion, and hyperarousal symptoms after a traumatic event) to assess the subjective stress caused by the specific event of COVID-19 (16)(17)(18)(19). The total scores of these measuring tools were categorized as follows: PHQ-9, normal (0-4), mild (5)(6)(7)(8)(9), moderate (10)(11)(12)(13)(14), and severe (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) depression; GAD-7, normal (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), and severe (15)(16)(17)(18)(19)(20)(21) anxiety; and IES-R, normal (0-8), mild (9)(10)(11)(12)(13)(14)…”
Section: Methodsmentioning
confidence: 99%